ЭКОЛОГИЧЕСКОЕ СОСТОЯНИЕ ВОДНОЙ И ВОЗДУШНОЙ СРЕДЫ ГОРОДА САМАРКАНДА - Маматқулов, Ж. Ж; Боймуродов , Х. Т; Эгамқулов , А. Н. (Actual problems and prospects of the study of the fauna, 2024)
An analysis of the dynamics of air pollution in the city in recent years shows that the content of ammonia and formaldehyde in the air tends to remain unchanged. Samarkand belongs to the category of cities with a predominant contribution of vehicle emissions into the atmosphere. Which currently accounts for about 90% of all emissions. The imperfection of the city's transport network and the high level of motorization lead to significant congestion of transport routes and pollution of the adjacent territories.